Las (TIC) y su influencia en el proceso de enseñanza-aprendizaje en la asignatura de matemática de los estudiantes de cuarto grado paralelo “A”, de la Unidad Educativa “Manuel Ignacio Monteros Valdivieso” de la ciudad de Loja, periodo académico 2021-2022 - Condolo Paqui, Luis Andrés (2023)
The incidence of information and communication technologies in the teaching-learning process of mathematics of students in fourth grade classroom A, at Manuel Ignacio Monteros Valdivieso primary school, of the city of Loja, through the academic period 2021-2022, had as a general objective to analyze the incidence of information and communication technologies in the teaching-learning process of mathematics of the students. A descriptive research was conducted using scientific, descriptive, observational, analytical, synthetic, inductive, deductive, statistical, hermeneutic techniques, and the survey was among the techniques used. The results indicate that ICT has played a significant role in the educational process, enabling the pedagogical subjects to better understand mathematics teaching. The participating sample consisted of 23 students and 1 teacher. Therefore, it is concluded that digital tools contribute positively in the realization of academic activities, in addition, the strategies used by the teacher have favored in a remarkable way the mathematical ability. Key words: Mathematics, Teaching, Learning, Education, Information and communication technologies.